Business Control System on Performance of Small and Medium Scale Enterprises (SMEs) in Ilorin Metropolis, Kwara State Nigeria - Yinusa Olawale; Ebenezer Balogun (Theory, Methodology, Practice, 2025)
Nigeria's unfledged physical as well as social infrastructure has hampered SMEs growth of the country. Many small and medium-sized businesses supply their own basic infrastructure; those that cannot do so are forced out of business or rely on inefficiently provided public infrastructure. As a result, this study investigates the influence of a business control system on SMEs performance in the Ilorin metropolitan area. The study specifically; (i) investigate the influence of cultural control on SMEs sustainability in Kwara State; and (ii) investigate the impact of administrative control on SMEs growth in Kwara. Descriptive design was used. A straightforward random sample strategy was used to get the study's data. 278 of the 313 questionnaires that were given to the chosen SME owners or managers were completely filled out, recovered, and utilized in this investigation. The data gathered was experimentally and statistically assessed using descriptive as well as inferential statistics, and the hypotheses were tested using Statistical Products and Services Solutions (SPSS) version 23. Findings revealed administrative control variables have a substantial influence on SMEs' development (Belief [β=.360, p=.000], Values [β=.214, p=.000], and Norms [β=.494, p=.000]; with overall R2 of 86.5%,) and cultural control has a considerable impact on SMEs' sustainability (Organizational structure control [β=.189, p=.000], Vision/Mission Control [β=.218, p=.000], and Governance System Control [β=.491, p=.000]; with overall R2 of 82.6%). The study indicated that business control systems had a beneficial impact on the performance of SMEs. It was suggested, among other things, that SME owners use cultural control in their enterprises to guarantee that their employees share the same perspective and focus, norms, and values as the organization's aims, since this contributes to the sustainability of SMEs.